Deciphering the Crystal Structure of a Scarce 1D Polymeric Thorium Peroxo Sulfate. Issue 41 (3rd July 2019) - Bonato, Laura; Virot, Matthieu; Dumas, Thomas; Mesbah, Adel; Lecante, Pierre; Prieur, Damien; Le Goff, Xavier; Hennig, Christoph; Dacheux, Nicolas; Moisy, Philippe; Nikitenko, Sergey I.
Abstract: The preparation and structural characterization of an original Th peroxo sulfate dihydrate, crystallizing at room temperature in the form of stable 1D polymeric microfibres is described. A combination of laboratory and synchrotron techniques allowed solution of the structure of the Th(O2 )(SO4 )(H2 O)2 compound, which crystallizes in a new structure type in the space group Pna 21 of the orthorhombic crystal system. Particularly, the peroxide ligand coordinates to the Th cations in an unusual μ3 ‐η 2 :η 2 :η 2 bridging mode, forming an infinite 1D chain decorated with sulfato ligands exhibiting simultaneously monodentate and bidentate coordination modes. Abstract : Mighty thorium : Structural characterization of an original Th peroxo sulfate dihydrate, crystallizing at room temperature in the form of stable 1D polymeric microfibers is described (see figure). Th(O2 )(SO4 )(H2 O)2 crystallizes in the Pna 21 space group of the orthorhombic system. Peroxide ligands coordinate to Th cations with a scarce μ 3 ‐ η 2 : η 2 : η 2 bridging mode forming infinite 1D chains decorated with monodentate and bidentate sulfato ligands.